A conceptual model of the influence of South African investor well-being on risk tolerance - R. W. Masenya; Zandri Dickason Koekemoer (Cogent Economics & Finance, 2020)
Financial institutions have the responsibility to measure an investor's risk tolerance to determine his or her risk profile. Once an investor's risk profile is determined, financial institutions are able to more accurately identify which financial products are suitable for the investor. Several factors can affect one's level of risk tolerance such as investor well-being. The aim of this study is to construct a structural equation model which depicts the influence of South African investor well-being risk tolerance. Secondary data analysis was used to conduct a quantitative research study. Structural equation modelling techniques were applied during the analysis of the data. The main findings suggest the following: (i) risk tolerance has a positive and statistically significant relationship with investor well-being; (ii) financial well-being has a positive and statistically significant relationship with satisfaction with life; and (iii) financial well-being, physical activity, gender, and income respectively have positive and statistically significant relationships with risk tolerance. Satisfaction with life was not found to have a statistically significant impact on risk tolerance.
Keywords: E02; G17; I31; 330; risk tolerance; investor well-being; structural equation model; South Africa